Entrepreneurship and employabiblity: the role of gender - Iglesias-Sánchez, Patricia Pilar; Santos Jaén, José Manuel; Jambrino-Maldonado, Carmen (ESU NETWORK, 2022)
A global concern about youth employment and the challenges to better connect companies’ needs and professional and labour profiles of graduates is shared by policy makers and higher education institutions. The recognition of entrepreneurship as an integral and sustainable part of the solution is a source of motivation for the incorporation of entrepreneurial competencies onto university curricula. The driving force of this study is to analyse how and to what extent the employability weighs on entrepreneurship. A Partial Least Squares Structural Equation Modeling (PLS-SEM) is applied using a survey that links Employability and Entrepreneurial Intention positively and highlights the moderating effect of gender. Our study contributes to research showing the interconnection between both and provides an insight from a gender approach. Women feel competences related to entreprising people are useful beyond business creation and they reinforce their self-confidence about their skills facing both entrepreneurial or employment objetives.
Keywords: Análisis multivariante - Congresos; Educación y empleo - Congresos; Nuevas empresas - Congresos; Mujeres - Trabajo - Congresos; Employability; Entrepreneurship; Entrepreneurial intention; Gender; PLS-SEM; Higher Education